Effect of Varying Degrees of Hepatic Impairment on the Pharmacokinetics of Omecamtiv Mecarbil. Issue 12 (9th June 2021) - Trivedi, Ashit; Oberoi, Rajneet K.; Mackowski, Mia; Jafarinasabian, Pegah; Zhang, Hanze; Flach, Stephen; Hutton, Shauna; Abbasi, Siddique; Dutta, Sandeep; Lee, Edward
Abstract: Omecamtiv mecarbil (OM) is a novel selective cardiac myosin activator under investigation for the treatment of heart failure with reduced ejection fraction. OM is primarily eliminated via metabolism mediated by multiple cytochrome P450 enzymes. This phase 1 single‐dose, multicenter, open‐label, nonrandomized study evaluated the pharmacokinetics (PK) of OM and major metabolites M3 and M4, safety, and tolerability following oral administration of a single dose of 25‐mg MR tablet in subjects with mild (n = 6) or moderate (n = 6) hepatic impairment (according to Child‐Pugh classification) versus subjects with normal hepatic function (n = 6). Relative to subjects with normal hepatic function, for subjects with mild or moderate hepatic impairment, OM AUCinf was 103.2% (90%CI, 58.0%‐183.6%) and 94.8% (90%CI, 54.7%‐164.1%), respectively, and OM Cmax was 126.8% (90%CI, 85.7%‐187.7%) and 117.3% (90%CI, 80.7%‐170.5%), respectively. Exposures to M3 were similar across groups, whereas slightly lower exposures were observed for M4 with worsening hepatic function. The OM, M3, and M4 tmax and t1/2 values were similar between groups. There were no serious adverse events (AEs) or treatment‐related treatment‐emergent AEs. Overall, OM, M3, and M4 PK were not meaningfully affected by mild or moderate hepatic impairment, suggesting the same dosing strategy can be used in subjects with mild or moderate hepatic impairment.